The problem of adopting agricultural production technologies: An analysis of gender-based power relations in the District of Barué, Mozambique (Research, Society and Development, 2024)
This article aims, through qualitative research, to make its contribution to understanding the power relations between men and women in the decision-making process for the adoption of agricultural technologies. The research was carried out in the district of Barué, province of Manica, Mozambique, and the study included 12 family producers integrated into the Escola na Machamba do Camponês (EMC), which is a technology transfer mechanism adopted by the United Nations Food Fund. (FAO) to transfer climate change-resilient agricultural technologies to farmers in the central region of Mozambique. The study reveals the existence of several spaces for the exercise of power and sharing of responsibilities between women and men when it comes to deciding on the adoption of a certain technology. The nature and type of technology are determining factors in the exercise of decision-making power.